The meaning of humanized nursing care for those participating in it: Importance of efforts of nurses and healthcare institutions (2016)
ABSTRACT: This study sought to understand this study sought to understand the meaning of the experience of humanized nursing care from the perspective of patients, relatives, and nurses. Methods.This was an interpretative phenomenological study that included 16 adult participants and which was based on indepth interviews to gather the information and on the procedures proposed by Cohen, Kahn, and Steeves to analyze the information. Results. Efforts by healthcare institutions and nurses are key elements to advance from impersonal care toward humanized care because these will permit revising and eliminating the barriers present in the current exercise of caring. The results highlight the importance of the effort for humanized behavior from nurses, given that because they are human beings their behavior in the relationship with patients is not always have that connotation. Conclusion. Humanized care is not only supported on the human condition of nurses or on the institutional intentions, but on attitudes and on a disposition focused on the patient’s well being. Additionally, tensions in nursing care are solved through humanizing efforts.